Minocycline prevents hypoxia-induced seizures - Fukushi, Isato; Ikeda, Keiko; Takeda, Kotaro; Yoshizawa, Masashi; Kono, Yosuke; Hasebe, Yohei; Pokorski, Mieczyslaw; Okada, Yasumasa (Frontiers in Neural Circuits, 2023)
Severe hypoxia induces seizures, which reduces ventilation and worsens the ictal state. It is a health threat to patients, particularly those with underlying hypoxic respiratory pathologies, which may be conducive to sudden unexpected death in epilepsy (SUDEP). Recent studies provide evidence that brain microglia are involved with both respiratory and ictal processes. Here, we investigated the hypothesis that microglia could interact with hypoxia-induced seizures. To this end, we recorded electroencephalogram (EEG) and acute ventilatory responses to hypoxia (5% O2 in N2) in conscious, spontaneously breathing adult mice. We compared control vehicle pre-treated animals with those pre-treated with minocycline, an inhibitory modulator of microglial activation. First, we histologically confirmed that hypoxia activates microglia and that pre-treatment with minocycline blocks hypoxia-induced microglial activation. Then, we analyzed the effects of minocycline pre-treatment on ventilatory responses to hypoxia by plethysmography. Minocycline alone failed to affect respiratory variables in room air or the initial respiratory augmentation in hypoxia. The comparative results showed that hypoxia caused seizures, which were accompanied by the late phase ventilatory suppression in all but one minocycline pre-treated mouse. Compared to the vehicle pre-treated, the minocycline pre-treated mice showed a delayed occurrence of seizures. Further, minocycline pre-treated mice tended to resist post-ictal respiratory arrest. These results suggest that microglia are conducive to seizure activity in severe hypoxia. Thus, inhibition of microglial activation may help suppress or prevent hypoxia-induced ictal episodes.